Clinical-epidemiological profile of the oncogeriatric patient served in high complexity public hospitals in the State of Pará in the historical series 2014-2018 (Research, Society and Development, 2020)
Introduction: Cancer is classified as a set of cells that have a disordered growth and without specific functions, in which they affect the systems, being that the main population affected is the elderly, due to the associated risk factors, being highlighted the process of cell aging. Objective: to trace the clinical-epidemiological profile of the oncogeriatric patient seen in public hospitals of high complexity in the State of Pará, in the 2014-2018 historical series. Methodology: This is an epidemiological, descriptive retrospective study with a quantitative approach. The study was carried out in the month of June 2020 with information from secondary data, coming from the Hospital Cancer Registry Computerization System for oncogeriatric patients seen in high complexity hospitals in the state of Pará in the period from 2014 to 2018. Results: if the total of 8,184 oncogeriatrics patients seen in hospitals in Pará and the distribution of sociodemographic data found the predominance of the male population, in the age group between 60 and 69 years old, brown race, most have only incomplete fundamental level. Conclusion: It is necessary for professionals to carry out health education practices for this public, in order to raise awareness and encourage self-care, so that these rates are overcome and they can age with a better quality of life.